Afghanistan at transition l essons of the longest war - Cordesman, Anthony H.; Lin, Aaron (CSIS report, 2015)
"This new study covers the civil and military lessons of the war in Afghanistan as of 2015, the trends at the time of transition, and the risks inherent in the current approach to supporting Afghanistan. The report focuses on the lessons to be learned from the US experience in Afghanistan to date and the problems Afghanistan faces now that most US and allied combat forces have left. The work builds on more than a decade's worth of reporting and analysis of the Afghan war. It examines the recent trends and problems in Afghan governance, trends in the fighting, progress in the Afghan security forces, and what may be a growing crisis in the Afghan economy. The analysis is supported with extensive metrics on every major military and civil aspect of the war, a detailed analysis of the fighting, and a close examination of the problems resulting from the lack of Afghan political unity, the growing Afghan budget crisis, and critical problems with power brokers and corruption"--Publisher's web site